OmpA-LC CUTINASE FUSION as Whole Cell Biocatalyst in Escherichia coli BL21 (DE3) DEGRADING Polyethylene Terphthalate (PET) - Ekawati Heryanto, Tri
terephthalate (PET) has been used widely, ranging from domestic to industrial use. PET is produced and consumed continuously, therefore it causes a buildup of plastic waste in the environment. This build up of plastic waste can be reduced by recycling and degradation of PET. Degradation of PET can be performed using a cutinase enzyme that has the ability like esterase which break the ester bond in the PET structure. PET particle can not enter into the cells of bacteria, the enzymes must be located extracellularly. The fusion of LC-Cutinase with OmpA would cause the LC-Cutinase to be bound to the surface of the cell facing outward. This would form a whole cell biocatalyst that is expected to be easier and more practical to use because it does not have to go through the protein purification process that take time and costs. The aim of this study is to clone fusion OmpA-LC Cutinase and LC-Cutinase activity assay at the optimum condition. The OmpA-LC Cutinase sequences that have been cloned into plasmid pJET 1.2/Blunt contained mutations at the base 261. Site Directed Mutagenesis (SDM) was used to repair the sequence. Three methods in SDM, are: Quick-change, Overlap and Inverse PCR. All methods are based on the PCR technique, which is used primers to change the target mutated sequences. The Quick-change method used forward and reverse primers that completely complement, with a base target at the center of the primer. Overlap method, forward and reverse primers only complement at the few sequences in the 5 'primer, with a mutation base target located in the overlap region. Inverse PCR, forward and reverse primers are not complement each other and the mutation target base only in the forward primer. The products are linear-shaped, that require ligation stage at the end of the mutation process. Overlap method shows the best SDM method to change the base target. LC-Cutinase activity assay in optimum condition, 50°C and pH 8.5 with four sample treatments. The culture has reached OD600 0,6 then certifuged, the supernatant used as non-sonication supernatant sample and the pellet as non-sonication pellet sample. The half of non-sonication pellet was resuspended and the cells lysed, then centrifuged to make sonication supernatant and pellet sample. The result showed the highest activity in sonication pellet, 5,479 units/ml of enzyme. However, there are also activities on a sample non-sonication pellet and sonication supernatant. While the results of SDS-PAGE with activity staining using p-nitrophenyl butyrate (PNPB) shows the band activity in the sample non-sonicated pellet, sonication supernatant and pellet with a size between 25-35 kDa. Through these results, it can be concluded that the LC-Cutinase showed the activity on the cell surface as a Whole cell biocatalyst, although there is activity inside the cell (intracellular). Further tests needed to optimize whole cell biocatalyst LC-Cutinase system and determine a direct impact on PET.